UNDERSTANDING THE INFLUENCE OF AMERICAN PUBLIC OPINION ON DOMESTIC POLICY FORMATION - HADJAIDJI, Messaouda; HAMARHOUM, Zoulikha (University of Eloued جامعة الوادي, 2024)
This research explores how American public opinion influences domestic policy choices by analyzing historical and modern instances to understand how public opinion affects policy results and the various elements that influence this connection. The research goal is to recognize and examine how public opinion is impacting, and combined in the formulation of domestic policies. It studies how elected officials and government institutions respond to changes in public opinion, and evaluate how much public sentiment influences policy agendas and decision-making procedures. Moreover, the research will investigate how media, interest groups, and public opinion polls impact public perceptions and policy results. The importance of this research is in its capacity to examine essential inquiries about how democracy operates, government responsiveness, and the influences on policy-making The study suggests that the opinions of the broader population are essential in influencing internal policies, prompting policymakers to take public preferences into account when making decisions. Data of the results had gathered and analyzed through a qualitative research which involves reviewing literature, analyzing case studies, and drawing conclusions to make recommendations. The results indicate that the opinions of American citizens are essential in influencing domestic policies in the United States, with political figures, the media, and the issue's significance all playing significant role. Public opinion is usually taken into account by elected officials and policymakers when creating and executing policies, especially for important issues when the public opinion is paying attention. . In summary, policymaking in the United States is significantly impacted by public opinion. Nevertheless, the impact differs among different sectors and tiers of government. يستكشف هذا البحث كيفية تأثير الرأي العام الأمريكي على خيارات السياسة الداخلية من خلال تحليل الأمثلة التاريخية والحديثة لفهم كيفية تأثير الرأي العام على نتائج السياسة والعناصر المختلفة التي تؤثر على هذا الارتباط. هدف البحث هو التعرف على ودراسة كيفية تأثير الرأي العام ودمجه في صياغة السياسات المحلية. وهو يدرس كيفية استجابة المسؤولين المنتخبين والمؤسسات الحكومية للتغيرات في الرأي العام، وتقييم مدى تأثير المشاعر العامة على جداول أعمال السياسات وإجراءات صنع القرار. علاوة على ذلك، سيبحث البحث في كيفية تأثير وسائل الإعلام ومجموعات المصالح واستطلاعات الرأي العام على التصورات العامة ونتائج السياسات. تكمن أهمية هذا البحث في قدرته على فحص الاستفسارات الأساسية حول كيفية عمل الديمقراطية، واستجابة الحكومة، والتأثيرات على صنع السياسات. وتشير الدراسة إلى أن آراء السكان الأوسع ضرورية في التأثير على السياسات الداخلية، مما يدفع صناع السياسات إلى اتخاذ قرارات عامة التفضيلات في الاعتبار عند اتخاذ القرارات. تم جمع بيانات النتائج وتحليلها من خلال بحث نوعي يتضمن مراجعة الأدبيات وتحليل دراسات الحالة واستخلاص النتائج لتقديم التوصيات. تشير النتائج إلى أن آراء المواطنين الأمريكيين ضرورية في التأثير على السياسات الداخلية في الولايات المتحدة، حيث تلعب الشخصيات السياسية ووسائل الإعلام وأهمية القضية دورًا مهمًا. عادة ما يتم أخذ الرأي العام في الاعتبار من قبل المسؤولين المنتخبين وصانعي السياسات عند إنشاء السياسات وتنفيذها، وخاصة بالنسبة للقضايا المهمة التي ينتبه إليها الرأي العام. . باختصار، يتأثر صنع السياسات في الولايات المتحدة بشكل كبير بالرأي العام. ومع ذلك، فإن التأثير يختلف بين مختلف القطاعات ومستويات الحكومة.
Literature and Civilization
Keywords: American Public Opinion; Citizens; Domestic policy; Polls; Political Decision-Making; الرأي العام الأمريكي، المواطنون، السياسة الداخلية، استطلاعات الرأي، اتخاذ القرار السياسي